Compliance with International Financial Reporting Standards (IFRSs) in a Developing Country: Evidence from Malaysia - Abdullah, Mazni; Sulaiman, Noor Adwa; Ismail, Kamisah; Sapiei, Noor Sharoja (Asian Journal of Accounting Perspectives, 2012)
There are three objectives of this study; first, to examine the level of compliance with the requirements of IFRS disclosure of Malaysian corporations; second, to identify which IFRS are problematic to comply with by the majority of Malaysian corporations; and, third, to understand why Malaysian corporations have difficulty in complying with the identified problematic IFRS. To achieve these objectives, we examine the annual reports of public listed companies and interview the accounting practitioners. Our results show that none of the examined companies fully complies with the requirements of IFRS disclosure. In addition, three IFRS are identified as problematic – accounting standards on impairment of assets, leases and employee benefits. Overall, this study demonstrates that the mere adoption of IFRS does not necessarily mean that the financial reports are transparent.